2014
DOI: 10.5114/wiitm.2014.44138
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery for early rectal cancer: single center experience.

Abstract: IntroductionThe use of transanal endoscopic microsurgery (TEM) is increasing due to the ability to perform minimally invasive local treatment with large full-thickness local excision under improved vision.AimTo evaluate the initial experience with TEM for early rectal cancer in a single center.Material and methodsFrom February 2010 to November 2013 a total of 20 patients underwent TEM for early rectal cancer. Nine were women and 11 men, age range 39 to 88 years (median: 71 years). The postoperative surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In conclusion, previous studies at our clinic had already shown TEM to be an alternative to the transanal approach when treating patients with benign and malignant rectal masses, and since those studies, it has become the procedure of choice for the treatment of patients with rectal tumors [ 28 29 ]. Acceptable short-term outcomes—low recurrence rates and low complication rates after the surgery—allow us to conclude that TEM is an effective and safe method for the treatment of patients with rectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, previous studies at our clinic had already shown TEM to be an alternative to the transanal approach when treating patients with benign and malignant rectal masses, and since those studies, it has become the procedure of choice for the treatment of patients with rectal tumors [ 28 29 ]. Acceptable short-term outcomes—low recurrence rates and low complication rates after the surgery—allow us to conclude that TEM is an effective and safe method for the treatment of patients with rectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, safe performance of STARR technique with clear resection margins was also very questionable. The TEM was therefore employed as the optimal surgical technique, allowing excellent access to rectal lesions located far away from the anal verge [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TEM provides a safe and effective way of full thickness excision of the rectal wall with a 1-cm margin. The technique facilitates the surgical approach to rectal lesions and allows rectal resection with a clear and detailed view [ 14 , 15 ]. Excellent haemostasis can be achieved efficiently using ultrasonic dissection; the rectal wall defect is closed safely and precisely.…”
Section: Discussionmentioning
confidence: 99%